Predisposition to Apoptosis in Hepatocellular Carcinoma: From Mechanistic Insights to Therapeutic Strategies - Marquardt, Jens U.; Edlich, Frank (Frontiers in Oncology, 2019)
Hepatocellular carcinoma (HCC) ranks among the most rapidly evolving cancers in the Western world. The majority of HCCs develop on the basis of a chronic inflammatory liver damage that predisposes liver cancer development and leads to deregulation of multiple cellular signaling pathways. The resulting dysbalance between uncontrolled proliferation and impaired predisposition to cell death with consecutive failure to clear inflammatory damage is a key driver of malignant transformation. Therefore, resistance to death signaling accompanied by metabolic changes as well as failed immunological clearance of damaged pre-neoplastic hepatocytes are considered hallmarks of hepatocarcinogenesis. Hereby, the underlying liver disease, the type of liver damage and individual predisposition to apoptosis determines the natural course of the disease as well as the therapeutic response. Here, we will review common and individual aspects of cell death pathways in hepatocarcinogenesis with a particular emphasis on regulatory networks and key molecular alterations. We will further delineate the potential of targeting cell death-related signaling as a viable therapeutic strategy to improve the outcome of HCC patients.